2006
DOI: 10.1124/jpet.105.099739
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Endothelium-Derived Hyperpolarizing Factor-Mediated Relaxations Attenuate Endothelial Dysfunction in Femoral and Mesenteric, but Not in Carotid Arteries from Type I Diabetic Rats

Abstract: Individual vascular beds exhibit differences in vascular reactivity. The present study investigates the effects of streptozotocininduced type I diabetes on endothelium-dependent responses of rat carotid, femoral, and mesenteric arteries. Rings with and without endothelium, suspended in organ chambers for isometric tension recording, were contracted with phenylephrine and exposed to increasing concentrations of acetylcholine. In carotid and femoral arteries, acetylcholine produced concentration-and endothelium-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
48
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 35 publications
(33 reference statements)
3
48
0
1
Order By: Relevance
“…Specifically, in diabetic animals evidence suggests both increased and decreased EDHF-mediated response (29). There are reports of increased EDHF activity in the mesenteric arteries of diabetic animals (64,75), and it has been proposed that EDHF may serve as a backup vasodilator in situations associated with an altered bioavailability of NO (8,52). Nevertheless, a decrease in EDHF-mediated response has also been reported in the mesenteric and renal arteries (17,28,49,95).…”
Section: Vs C)mentioning
confidence: 88%
See 1 more Smart Citation
“…Specifically, in diabetic animals evidence suggests both increased and decreased EDHF-mediated response (29). There are reports of increased EDHF activity in the mesenteric arteries of diabetic animals (64,75), and it has been proposed that EDHF may serve as a backup vasodilator in situations associated with an altered bioavailability of NO (8,52). Nevertheless, a decrease in EDHF-mediated response has also been reported in the mesenteric and renal arteries (17,28,49,95).…”
Section: Vs C)mentioning
confidence: 88%
“…Wigg et al (95) reported a preserved NO-dependent response, but an impaired EDHF-dependent response in femoral and mesenteric arteries. On the other hand, Shi et al (75) described a reduced NO-mediated response and an enhanced EDHF-mediated response in mesenteric arteries of diabetic rats. Finally, Leo et al (45) reported both impaired NO-and EDHF-mediated relaxation in the same arteries.…”
mentioning
confidence: 99%
“…The effect of STZ-induced diabetes on nitric oxidemediated vasodilatation is still controversial; it has been reported as normal in the aorta (Head et al, 1987;Harris and MacLeod, 1988;Mulhern and Docherty, 1989), mesenteric artery (Harris and MacLeod, 1988) and femoral artery (Wigg et al, 2001), as blunted in aorta (Pieper et al, 1997;Vallejo et al, 2000), mesenteric artery (Heygate et al, 1995;Vallejo et al, 2000;Shi et al, 2007) and femoral artery (Shi et al, 2006) or augmented in aorta (Altan et al, 1989). The production of vasoconstrictor prostaglandins is augmented in diabetic animals (aorta , renal artery (Pflueger et al, 1999) and femoral artery (Shi et al, 2007)).…”
Section: Introductionmentioning
confidence: 99%
“…Altered endothelial function is associated with animal models of type I diabetes (Shi et al, 2006), type II diabetes (Park et al, 2008), pulmonary hypertension (Kemp et al, 1995), hypercholesterolemia (Brandes et al, 1997), heart failure (Katz and Krum, 2001), and aging (Gaubert et al, 2007), where NO activity is reduced, and K Ca -mediated EDH is preserved or up-regulated to maintain overall vasodilation. The disease-related effects of endothelium-dependent vasodilation in diet-induced obesity are unknown.…”
Section: Introductionmentioning
confidence: 99%